2021
DOI: 10.1097/hmr.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with difficulty in adapting and intent to leave among new graduate nurses in South Korea

Abstract: BackgroundNew graduate nurses experience difficulty in adapting to a new environment, which affects intent to leave. However, data on the factors contributing to difficulty in adapting and intent to leave among new graduate nurses are insufficient.PurposeThe aim of the study was to explore and compare factors associated with difficulty in adapting and the intent to leave among new graduate nurses in South Korea.MethodologyThis cross-sectional study used secondary data analysis. Primary data were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Notably, few international studies reported wages as a pull factor for early-career nurses 47 48. In contrast, job dissatisfaction49 50 and poor working conditions,51 52 including job stress37 53 and a higher level of transition shocks40 54 increase the intention to leave of early-career nurses. There is also evidence that the lack of team support,55 lack of vocation55 56 or feeling of inadequacy52 increase the turnover likelihood among early-career nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, few international studies reported wages as a pull factor for early-career nurses 47 48. In contrast, job dissatisfaction49 50 and poor working conditions,51 52 including job stress37 53 and a higher level of transition shocks40 54 increase the intention to leave of early-career nurses. There is also evidence that the lack of team support,55 lack of vocation55 56 or feeling of inadequacy52 increase the turnover likelihood among early-career nurses.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the lack of team support,55 lack of vocation55 56 or feeling of inadequacy52 increase the turnover likelihood among early-career nurses. Recent international studies have also shown that male nurses report a higher level of intention to leave compared with female nurses 49 51 57…”
Section: Introductionmentioning
confidence: 99%